Push and pull factors of nurses' intention to leave. (21st April 2019) - Sasso, Loredana; Bagnasco, Annamaria; Catania, Gianluca; Zanini, Milko; Aleo, Giuseppe; Watson, Roger
Abstract: Aim: To expand knowledge about the predictive factors of nurses' intention to leave their job and consequently to turnover. Background: Nurse turnover is costly and negatively influences quality of care. Understanding the association between intention to leave and modifiable features of hospital organisation may inform strategies to reduce turnover. Methods: A cross‐sectional survey of 3, 667 medical and surgical nurses was conducted in Italy. Measures included intention to leave; work environment; burnout; job satisfaction; and missed care using the RN4CAST instruments. Descriptive, logistic regression analysis was used. Results: Due to job dissatisfaction, 35.5% of the nurses intended to leave their current job, and of these, 33.1%, the nursing profession. Push factors included the following: understaffing, emotional exhaustion, poor patient safety, performing non‐nursing care and being male. Pull factors included the following: positive perception of quality and safety of care, and performing core nursing activities. Conclusion: The present study expands knowledge about the predictive factors of nurses' intention to leave their job and consequently to turnover, which is one of today's major issues contributing to the shortage of nurses. Implications for Nursing Management: Nurses' intention to leave their job is the consequence of a poor work environment, characterized by factors such as understaffing and performance of non‐nursing activities.